1984
DOI: 10.1128/iai.45.3.685-691.1984
|View full text |Cite|
|
Sign up to set email alerts
|

Vaccination against Legionella pneumophila: serum antibody correlates with protection induced by heat-killed or acetone-killed cells against intraperitoneal but not aerosol infection in guinea pigs

Abstract: An aerosol model of Legionella infection has been established in guinea pigs. Infected animals showed growth of Legionella in their lungs, dissemination of organisms to the spleen, development of pneumonia and fever, and weight loss. Vaccination studies using heat-killed or acetone-killed cells were carried out, and guinea pigs were challenged intraperitoneally or by using the aerosol model of infection. Both vaccines were shown to give moderately high levels of protection against intraperitoneal challenge (28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…We have demonstrated that sublethal infection with L. pneumophila produced protective immunity in vivo against this intracellular pathogen. Moreover, we have demonstrated that sublethal infection with L. pneumophila by the airborne route, the natural route of infection, protects against lethal challenge by this Previous studies have failed to demonstrate protective immunity to L. pneumophila in vivo (12,13). We believe this is because the challenge doses in those studies were so high that they overwhelmed the capacity of the immune system to counteract the challenge.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…We have demonstrated that sublethal infection with L. pneumophila produced protective immunity in vivo against this intracellular pathogen. Moreover, we have demonstrated that sublethal infection with L. pneumophila by the airborne route, the natural route of infection, protects against lethal challenge by this Previous studies have failed to demonstrate protective immunity to L. pneumophila in vivo (12,13). We believe this is because the challenge doses in those studies were so high that they overwhelmed the capacity of the immune system to counteract the challenge.…”
Section: Discussionmentioning
confidence: 87%
“…(12), sublethally infected guinea pigs were challenged with 10 times the LD5o and not protected. In the study by Eisenstein et al (13), guinea pigs surviving a previous infection were challenged with 44 times the LD5o and were not protected.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear whether humans who have had Legionnaires disease are then immune to reinfection. Guinea pigs that have been immunized with killed L. pneumophila antigen are protected against subsequent intraperitoneal challenge, but not against aerosol infection (79). Surprisingly, Baskerville and co-workers were unable to protect guinea pigs that had been previously infected by aerosol against subsequent inhalation of a bacterial aerosol (10); in fact, the previously infected animals died somewhat sooner than their naive counterparts.…”
Section: Recovery and Immunitymentioning
confidence: 99%
“…L. pneumophila serogroup 1 and strain A5H5 were both virulent by this model and caused death in 3 of 5 animals tested. Examination of the lungs taken from a guinea pig that died due to exposure to A5H5 revealed that the air spaces of the lung parenchyma were filled with a dense cellular infiltrate consisting of neutrophils and monocyte cells, and the histological appearance was consistent with a severe acute pneumonia similar to that seen with L. pneumophila serogroup 1 (3,4,15). Animals exposed to aerosols of L. longbeachae serogroup 1 ATCC 33462 and L. longbeachae serogroup 2 ATCC 33484 developed no symptoms and were avirulent, although the numbers of Legionella organisms retained in the lung with each test strain were comparable (Table 3).…”
Section: Effect Of Mip On Intracellular Infectionmentioning
confidence: 91%